A study on the status of fluoride ion in groundwater of coastal hard rock aquifers of south India - Singaraja, C.; Chidambaram, S.; Anandhan, P.; Prasanna, Mohan Viswanathan; Thivya, C.; Thilagavathi, R. (Springer, 2013)
India has an increasing incidence of fluorosis, dental and skeletal, with nearly about 62 million people at risk. High fluoride groundwaters are present especially in the hard rock areas of the country. This paper analyzes the most extensive database on fluoride and other chemical constituent distribution in the coastal hard rock aquifers of Thoothukudi district. A total of 135 samples were collected and analyzed for major cations and anions to assess the geochemical process. The fluoride concentration in drinking waters varied from BDL to 3.2 mg l-1 in the study area. Majority of the samples do not comply with WHO standards for most of the water quality parameters. The saturation index of fluorite saturation index was used to correlate with F- to identify their relationship to increase of fluoride levels. The correlation between the F- concentration and the water type was also attempted. Spatial distribution of fluoride in groundwater was studied to understand the influencing factors. The relationship of F- with HCO- 3, Na+ and pH concentrations were studied and found that HCO- 3, has good correlation with F- than the other parameters.